Scaling up delivery of HIV services in Africa through harnessing trends across global emerging innovations - Chibi, Moredreck; Wasswa, William; Ngongoni, Chipo Nancy; Lule, Frank (Frontiers in Health Services, 2023)
Globally, innovations for HIV response present exciting opportunities to enhance the impact and cost-effectiveness of any HIV program. However, countries especially in the African region are not on equal footing to effectively harness some of the existing innovations to accelerate impact on HIV services delivery. This paper aims to add to the discourse on innovative solutions to support countries to make informed decisions related to technologies that can be adapted in different contexts to strengthen HIV programs. A scoping review which involved a search of innovations that can be used in response to the HIV epidemic was carried out between June 2021 and December 2022. The results showed that a high level of technological advancement occurred in the area of digital technologies and devices. Out of the 202 innovations, 90% were digital technologies, of which 34% were data collection and analytics, 45% were mobile based applications, and 12% were social media interventions. Only 10% fell into the category of devices, of which 67% were rapid diagnostic tools (RDTs) and 19% were drone-based technologies among other innovative tools. The study noted that most of the innovations that scaled relied on a strong ICT infrastructure backbone. The scoping review presents an opportunity to assess trends, offer evidence, and outline gaps to drive the adoption and adaptation of such technologies in Africa.